Wine tourism experience in Azeitão - Sena, Maïté Leloup (2019)
Wine tourism is intensively growing all over the world. This sector is essential for the tourism industry of each country and can be a potential strategy to become a pole of interest for industry consumers. The dissertation’s goal is to identify the dimensions of wine tourism and understand how they are organized to potentialize a complete and satisfying experience for wine tourism consumers – wine tourists. By applying Quadri-Felitti and Fiore (2014) model, it became possible to understand the needs of wine tourists and to verify what is most relevant for them while engaging in wine tourism activities, in order to have input that allow wineries to increase their service and experience quality. These objectives were achieved by studying the different dimensions’ influence on the perceived wine tourism quality. To understand this phenomenon, a content analysis was applied with a netnography research on Azeitão wine tourist. The findings revealed that entertaining and educational dimensions are fundamental. And, that other dimensions such as esthetical appearance and the escapist still presented a gap between the needs of consumers and the actual offer presented by the wineries, which can be perceived as opportunities for improvements. The research on wine tourism experiences in Azeitão allowed to extract some valuable input for regional wine companies to improve their offer, making the tourism industry in Portugal to become even more relevant in the world.